Hubungan Dukungan Suami dengan Pemberian ASI Eksklusif - Silaen, Ribka Septiana; Novayelinda, Riri; Zukhra, Ririn Muthia (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2022)
Introduction: Husband support is an important factor that influences a mother's decision to give exclusive breastfeeding to their baby. Previous studies refer to the dimensions of husband's support, while research related to the relationship between husband's support and exclusive breastfeeding based on the husband's support component is still a little done and requires further research. The study aimed to examine the relationship of husband support needed by mothers with exclusive breastfeeding practice in the Simpang Tiga Health Care working area.Methods: The design of this study is a descriptive correlation with a cross-sectional study approach. The samples in this study were 89 participants taken using the purposive sampling technique with the inclusion criteria are mothers who are willing to be respondents, mothers who have babies aged 6 to 12 months, and mothers who have been given breast milk. Data analysis was performed by Chi-square test.Results: Main results distinguished that there is a relationship of husband support needed by mothers with exclusive breastfeeding practice p-value (0.015) < alpha (0.05). This is indicative that there is a significant relationship between husband support needed by mothers with exclusive breastfeeding practice.Conclusion: The husband's support needed by mothers has a relationship with exclusive breastfeeding practice. Husbands need to provide support to mothers during breastfeeding period because it can affect the amount of milk produced by mothers, affect the duration of exclusive breast feeding and affect the mother's choice of breastfeeding.